The pillars of school: a case study of middle leaders in four private secondary schools in Islamabad, Pakistan - Riaz, Saira (2019)
This is a qualitative case stiudy of four private secondry schools in Islamabad in Pakistan. This study focuses on roles, responsibilities and challenges of the middle leaders who work as subject heads, coordinaotrs and head of departments in schools. The middle leaders are involved in multitasking to upgrade the quality of schools but their efforts are not recognized. Through their attitudes, behaviour and leadership practices, they evolve traditional leadership of Pakistan.